Analisis Anggaran Belanja Daerah Pada Kabupaten/Kota di Provinsi Kalimantan Selatan Periode 2016-2020 - Mendrofa, Devi Yunika; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The purpose is to analyze the regional budget for regencies/cities in South Kalimantan province. They are analyzing the inhibiting factors in the South Kalimantan province's regencies/cities' provincial budget. And analyze what government policies are increasing regional spending in regencies/cities in South Kalimantan province. The type of data is secondary data (time series). This type of research is descriptive quantitative. The results showed that the average spending variance in ten regencies/cities was favored (Favourable Variance). Expenditure growth shows eight regencies/cities positive results. Expenditure compatibility shows a balanced operating expenditure and two regencies/cities show an unbalanced category; capital expenditures show capital expenditure shows balanced expenditure, but only two regencies show a balance. Expenditure efficiency shows mixed result tend to be less efficient. The inhibiting factors in the performance of the regional budget are budget planning factors, budget execution, and human resources. The government takes policies to improve spending performance.